Pengaruh Implementation of Green Accounting dan CSR Disclosure (Profitabilitas, Firm Size, Capital Structure Sebagai Variabel Kontrol) - Gita Hang Dano; Fauziyah (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to explain the effect of implementation of green accounting and CSR Disclosure on firm value with profitability, firm size, capital structure as control variables. This study uses a sample of 21 energy sector companies listed on the Indonesia Stock Exchange in the period 2021-2023. The data analysis technique used is quantitative data analysis including classical assumption tests, multiple regression analysis, and t-tests using SPSS. The results of this study provide evidence that implementation of green accounting and CSR Disclosure have a partial effect on firm value. Implementation of green accounting with profitability as a control, implementation of green accounting with firm size as a control variable, and CSR Disclosure with firm size as a control variable have a partial effect on firm value. Meanwhile, CSR Disclosure with profitability as a control, implementation of green accounting with capital structure as a control, and CSR Disclosure with capital structure as a control do not have a partial effect on firm value.